Experimental inoculation of Neospora caninum in pregnant water buffalo - Konrad, Jose Luis; Moore, Prando Dadin; Crudeli, Gustavo Angel; Caspe, Sergio Gaston; Cano, Dora Beatriz; Leunda, Maria Rosa; Lischinsky, Lilian Haydee; Regidor-Cerrillo, Javier; Odeon, Anselmo Carlos; Ortega-Mora, Luis M.; Echaide, Ignacio Eduardo; Campero, Carlos Manuel (Elsevier, 2019)
The aim of this study was to characterize the pathogenesis of Neospora caninum in experimentally inoculated pregnant water buffalo (Bubalus bubalis). Twelve Mediterranean female water buffaloes ranging in age from 4 to 14 years old and seronegative to N. caninum by indirect fluorescent antibody test (IFAT) were involved. Ten females were intravenously inoculated with 108 tachyzoites of NC-1 strain at 70 (n = 3) or 90 (n = 7) days of pregnancy (dp). Two control animals were inoculated with placebo at 70 and 90 dp, respectively. Serum samples were obtained weekly following inoculation to the end of the experiment. Three animals inoculated at 70 dp were slaughtered at 28 days post inoculation (dpi), three animals inoculated at 90 dp were slaughtered at 28 dpi and the remaining four animals inoculated at 90 dp were slaughtered at 42 dpi. Fetal fluids from cavities and tissue samples were recovered for IFAT and histopathology, immunohistochemistry and PCR, respectively. Genomic DNA from fetal tissues was used for parasite DNA detection and microsatellite genotyping in order to confirm the NC-1 specific-infection. Dams developed specific antibodies one week after the inoculation and serological titers did not decrease significantly to the end of the experiment. No abortions were recorded during the experimental time; however, one fetus from a dam inoculated at 70 dp was not viable at necropsy. Specific antibodies were detected in only two fetuses from dams inoculated at 90 dp that were slaughtered at 42 dpi. No macroscopic changes in the placentas and organs of viable fetuses were observed. Nonsuppurative placentitis was a common microscopic observation in Neospora-inoculated specimens. Microscopic fetal lesions included nonsuppurative peribronchiolar interstitial pneumonia, epicarditis and myocarditis, interstitial nephritis, myositis and periportal hepatitis. Positive IHC results were obtained in two fetuses from dams inoculated at 70 dp and slaughtered at 28 dpi. N. caninum DNA was detected in placentas and fetuses from all inoculated animals. The pattern of amplified microsatellites from placental and fetal tissues resembled the NC-1 strain. Water buffaloes, like cattle, are susceptible to experimental inoculation with N. caninum at early pregnancy.